Potential miscanthus' adoption in Illinois: Information needs and preferred information channels - Villamil, Maria Bonita (2008)
This study examined farmers' information needs and concerns and preferred information channels regarding the introduction of miscanthus in their current production systems in the state of Illinois, USA. Surveys and focus groups targeted farming populations from Northern, Central, and Southern regions of the state to evidence regional differences. A secondary objective was to identify potential adopters of miscanthus and to asses the level of awareness regarding miscanthus and the associated possibility of receiving carbon credits. Factor analysis, multivariate ANOVA, and categorical data analysis were the selected statistical tools. Only two out of 313 respondents knew about the existence of the crop before completing the survey. Thirty percent of the respondents were identified as potential adopters of miscanthus with the highest proportion of potential adopters found among farmers in the Northern Illinois region. There are clear differences among the information needs of farmers in each region in Illinois as well as in the preferred channels. Information campaigns aimed to increase awareness and education regarding the use of miscanthus as an energy crop in Illinois, should specifically address these regional information needs and channel them through preferred media.